WHO Year of the Nurse and Midwife: More clean and educated hands for all - Peters, Alexandra (J Infect Prev, 2020)
For the last 10 years, the World Health Organization has been celebrating World Hand Hygiene Day on the 5th of May, bringing together the global healthcare ecosystem to celebrate hand hygiene. This day was created to raise awareness about the importance of hand hygiene in healthcare settings, as well as to focus on a specific annual topic to be highlighted to a global audience. The World Health Assembly designated 2020 as the Year of the Nurse and Midwife, and the slogan of this year’s 5(th) of May was “Nurses and Midwifes: Clean Care is in Your Hands”. This 5th of May helped us to highlight the need for increased staffing and hand hygiene training. In this paper we aimed to raise awareness about the global impact linked to adherence to proper hand hygiene practices by nurses and midwives.